"Exports‐at‐Risk": The Effect of Multimarket Contact in International Trade. (23rd January 2015) - Feinberg, Robert M.
<x xml:space="preserve">Abstract</x> Despite a well‐established literature examining possible impacts on competition in oligopolistic markets from multimarket contact (MMC) among diversified firms, only recently have trade theorists considered the possible effects of MMC among exporters in limiting the anticipated procompetitive role of imports. This article presents a first effort to test the empirical importance of a measure of this MMC, called "exports‐at‐risk, " on import prices (unit‐values). Suggestive evidence of anticompetitive impacts of MMC among exporters is obtained for highly traded four‐digit harmonized system (HS) products within the broad category of "fats and oils." Exporters in fats and oils seem to price higher in markets where they meet rivals with the ability to retaliate against their "exports at risk."